The impact of the COVID-19 pandemic on perinatal services and maternal mental health in the UK. Issue 1 (13th January 2023) - Kasaven, Lorraine S.; Raynaud, Isabel; Jalmbrant, Maria; Joash, Karen; Jones, Benjamin P.
Abstract : Background: COVID-19 has created many challenges for women in the perinatal phase. This stems from prolonged periods of lockdowns, restricted support networks and media panic, alongside altered healthcare provision. Aims: We aimed to review the evidence regarding the psychological impact on new and expecting mothers following changes to antenatal and postnatal service provision within the UK throughout the pandemic. Method: We conducted a narrative literature search of major databases (PubMed, Medline, Google Scholar). The literature was critically reviewed by experts within the field of antenatal and perinatal mental health. Results: Changes to service provision, including the introduction of telemedicine services, attendance of antenatal appointments without partners or loved ones, and lack of support during the intrapartum period, are associated with increased stress, depression and anxiety. Encouraging women and their partners to engage with aspects of positive psychology through newly introduced digital platforms and virtual service provision has the potential to improve access to holistic care and increase mental well-being. An online course, designed by Imperial College Healthcare NHS Trust in response to changes to service provision, focuses on postnatal recovery inspiration and support for motherhood (PRISM) through a 5-week programme. So far, the course has received positive feedback. Conclusions: The pandemic has contributed to increased rates of mental illness among pregnant and new mothers in the UK. Although the long-term implications are largely unpredictable, it is important to anticipate increased prevalence and complexity of symptoms, which could be hugely detrimental to an already overburdened National Health Service.